A Digital Infrastructure Perspective for Accelerated Rural Entrepreneurship - Nteboheng Patricia Mefi; Samson Nambei Asoba (Contemporary Research in Business, Management and Economics Vol. 8, 2024)
Within the technological context associated with the Fourth Industrial Revolution (4IR) as well as the technological implications of the Covid-19 pandemic, digitalization has increased. Given that rural entrepreneurs have traditionally lagged behind in many facets of competitiveness, the purpose of this study was to explore the question: How can digital infrastructure accelerate small business entrepreneurship in a rural community in the Eastern Cape Province? The study was based on a qualitative design related to participant observations and document analysis. Participating in a meeting between entrepreneurs, academics and Small Enterprise Development Agency (SEDA) officials and analyzing the discussion areas and behaviours of participants allowed the objectives of the study to be achieved. It was found that virtual infrastructure development excited the respondents and inspired the business and developmental aspirations of participants. Participants provided that digital infrastructure development in rural Eastern Cape would foster economic development, close the digital divide, widen small enterprise development models, ensure inclusive economic participation and create new business opportunities. It was also provided that digital infrastructure creates entrepreneurial linkages that would promote business ecosystems in rural areas and foster general economic advancement in rural areas. This study resulted in the need to recommend government to increase digital support and investment in rural areas.